(untitled) (GIST – Education and Learning Research Journal, 2014)
This research study analyzes the literacy and foreign langauge processes of learners in the Procesos Básicos Program. The participants were 15 Spanishspeaking children and young adolescents, whose highest level of education was first grade. Eight of the 15 children were Internally Displaced Persons (IDPs), and the others were affected by violence, family issues, and cognitive difficulties. These groups of students attend a public school located in Bogotá Colombia. Most of the students have faced interrupted schooling due to different social factors. As a consequence, there are children of different ages and social backgrounds, including IDPs, in each classroom. Differentiation was used as well as GANAG (Goal, Activating Prior knowledge, New information, Aplication, Generalization) reading formats in both English as a foreign language (EFL) and Spanish (mother tongue) literacy classes. Results show that there was little impact of differentiated instruction on writing production or vocabulary acquisition. However, there was evidence of an impact on reading comprehension when inferring and comparing and contrasting narrative texts.